First report on the occurrence of CO2-bearing fluid inclusions in the Meiduk porphyry copper deposit, Iran: implications for mineralisation processes in a continental collision setting - Asadi, Sina; Moore, Farid; Zarasvandi, Alireza; Khosrojerdi, Majid (Geologos, 2014)
Hydrothermal alteration of the Meiduk porphyry copper deposit, south of the Kerman Cenozoic magmatic arc and southeast of the central Iranian volcano-plutonic belt has resulted in three stages of mineralisation characterised by veins and veinlets. These are, from early to late: (1) quartz + K-feldspar + biotite + pyrite ± chalcopyrite ± pyrrhotite ± magnetite (early potassic alteration and type-A veins); (2) quartz + chalcopyrite + pyrite + bornite + pyrrhotite + K-feldspar + biotite + magnetite (potassic-sericitic alteration and type-B veins); and (3) quartz + pyrite + chalcopyrite + sericite (sericitic alteration and type-C veins). Most ores were formed during stages 2 and 3. Three main types of fluid inclusions are distinguished based on petrographical, microthermometrical and laser Raman spectroscopy analyses, i.e. type I (three-phase aqueous inclusions), type II (three-phase liquid-carbonic inclusions) and type III (multi-phase solid inclusions). The fluid inclusions in quartz veins of the stages are mainly homogenised at 340–530°C (stage 1), 270–385°C (stage 2) and 214–350°C (stage 3), respectively, with salinities of 3.1–16 wt.% NaCl equivalent, 2.2–43 wt.% NaCl equivalent and 8.2–22.8 wt.% NaCl equivalent, respectively. The estimated trapping pressures are 97.9-123.6 MPa (3.7-4.6 km) in stage 1 and 62.5-86.1 MPa (2.3-3.1 km) in stage 2, respectively. These fluid inclusions are homogenised in different ways at similar temperatures, suggesting that fluid boiling took place in stages 2 and 3. The fluid system evolved from high-temperature, medium-salinity, high-pressure and CO2-rich to low-temperature, low-pressure, high-salinity and CO2-poor, with fluid boiling being the dominating mechanism, followed by input of meteoric water. CO2 escape may have been a factor in increasing activities of NaCl and S2- in the fluids, diminishing the oxidation of the fluids from stage 1 to 3. The result was precipitation of sulphides and trapping of multi-phase solid inclusions in hydrothermal quartz veins.